Peptide-based drug discovery tools for protein post-translational modifications - Eskonen, Ville (fi=Turun yliopisto|en=University of Turku|, 2021)
Bringing a new drug to the market is an expensive and long process. Typically, more than ten years and a billion dollars needs to be spent so the whole process is a big investment for a pharma company. The hit generation phase of the drug development is one of the first steps of the development and there, millions of potential molecules are screened against a known druggable target in order to generate hits, i.e., molecules that have a specific activity towards the target. The hit generation phase requires high throughput screening (HTS) assays that are capable of screening millions of molecules rapidly with low expenses with platforms that are robust. This thesis project focused on developing assays for hit generation phase for targets that catalyse protein post-translational modifications (PTMs). PTMs are regulatory mechanisms of cells that control many cellular events and are therefore involved in many disease conditions, for example, cancer. PTMs are additions or cleavages of chemical groups, typically catalysed by enzymes which activity can be affected with inhibitor or activator molecules. Today, the techniques available for the activity monitoring of PTM-catalysing enzymes suffer from many weaknesses. Many methods, such as mass spectrometry or heterogeneous luminescence-based techniques, are not applicable for HTS, which increases the screening times of molecule libraries and therefore the cost of screening. Alternatively, some techniques are developed for one of a few different PTMs and therefore requiring a new platform for each PTM. On top of these, many methods are expensive to perform due to low sensitivity or antibodies, making the development of new assays motivating. The work presented in this thesis expanded the Peptide-Break technology to be more well suited in PTM-detection and developed one new assay to detect cysteinespecific PTMs. The developed assays are simple homogeneous techniques applicable for HTS providing new interesting options for inhibitor screening.